2006
DOI: 10.1063/1.2166697
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced conductivity in graphene layers and at their edges

Abstract: We have observed that the conductivity of graphene sheets is higher whenever they are loosely bound to the underlying bulk graphite. We also observe that certain edges of the graphene layers show sharp rise in current when biased, indicating enhanced electronic density of states spatially localized near those edges. In certain edges, we do not observe this phenomenon. These two observations, i.e., enhancement of conductivity of loosely bound layers and sharp rise in current at the edges are discussed with poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 17 publications
4
41
0
Order By: Relevance
“…A distinct mobility reduction after top-gate deposition is observed that is attributed to the participation of the top π-orbitales to van der Waals bonds to the silicon dioxide. The resultant reduction of orbital overlap then leads to a reduced conductivity [7]. Despite the substantial mobility reduction after the top-gate deposition, graphene mobility exceeds the universal mobility of silicon almost over the entire measured range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A distinct mobility reduction after top-gate deposition is observed that is attributed to the participation of the top π-orbitales to van der Waals bonds to the silicon dioxide. The resultant reduction of orbital overlap then leads to a reduced conductivity [7]. Despite the substantial mobility reduction after the top-gate deposition, graphene mobility exceeds the universal mobility of silicon almost over the entire measured range.…”
Section: Discussionmentioning
confidence: 99%
“…It is further known that carrier transport in graphene takes place in the π-orbitals perpendicular to the surface [7]. Intrinsically this translates into charge carrier transport with a mean free path for carriers of L = 400 nm at room temperature [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the edges of graphene sheets from highly oriented pyrolitic graphite have been directly investigated by scanning tunneling microscopy (STM) in association with scanning tunneling spectroscopy (STS) [129 132] and by direct contact atomic force microscopy (AFM) [133,134]. Micro-Raman spectroscopy has also proved to be a valuable tool for studying the armchair or zigzag orientation of the ribbon edges locally [135].…”
Section: Nano Researchmentioning
confidence: 99%
“…Excellent electronic properties with reported carrier mobilities between 3000 and 27000 cm²/Vs make it an extremely promising material for future nanoelectronic devices [5] [7]. The carrier transport in graphene takes place in the π-orbitals perpendicular to the surface [8] and the extraordinary transport properties have been attributed to a single spatially quantized subband populated by electrons with a mass of m e 0.06 m 0 or by light and heavy holes with masses of m h 0.03 m 0 and m h 0.1 m 0 [5]. With a mean free path for carriers of L = 400 nm at room temperature, ballistic devices seem feasible, even at relaxed feature sizes compared to State-of-the-Art CMOS technology.…”
Section: Introductionmentioning
confidence: 99%